Determination of Heavy Metal Concentrations in Household Dusts in Irbid and Mafraq Cities, Jordan - Asmaa Ali Al-Serhan; "Ayat Allah" Al-Massaedh; Idrees Faleh Al-Momani (Indonesian Journal of Chemistry, 2023)
The objective of this study was to measure the concentrations of selected heavy metals (Pb, Cd, Zn, Cu, Fe, Cr, Co, Ni, and Mn) in house dust collected during the summer and winter seasons from Mafraq and Irbid cities, Jordan. The average concentrations (±SD) of the metals were found to be 66.8 (±22.4), 10.8 (±3.75), 366 (±108), 81.6 (±43.9), 7586 (±4304), and 37.2 (±15.4) mg/kg, for Pb, Cd, Zn, Cu, Fe, and Cr, respectively, in the summer season. The average concentrations (±SD) of the metals were found to be 92.8 (±65.5), 5.10 (±4.75), 305 (±160), 144 (±163), 5385 (±3812), 27.1 (±15.1), 18.7 (±3.70), 42.2 (±15.1), and 139 (±69.2) mg/kg, for Pb, Cd, Zn, Cu, Fe, Cr, Co, Ni, and Mn, respectively, in the winter season. The influence of different heating systems on the concertation of heavy metal was examined by comparing the results obtained in both summer and winter seasons. The concentrations of the metals in this study were compared with those reported by other researchers around the world. This study shows that the significant accumulation of heavy metals in house dust should be considered a serious risk to the health of residents in Mafraq and Irbid cities.